(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
This paper deals with some of the more characteristic moments which mark the state of Macedonia as a southern Serbian province in the early phases ofparliamentary life in the Kingdom of Serbs, Croats and Slovenes from 1919 to 1929. A brief overview of the periodfrom 1903 to 1918 is provided, an invaluable period without which there can neither be analysis of the Macedonian ‘lengthy ’ 20lh century, nor of the history of parliamentarism in Macedonia as a southern Serbian province. The denial of the Macedonian national particularity, the economic theft and the political violence all resulted in discontent among the whole of the Macedonian population, save some exceptions who were working for the Greater Serbian regime. The lack of economic development, as well as the lack of enlightenment evident in the Macedonian people due to the lengthy period of foreign rule over Macedonia, furthermore, the lack of democratic traditions and political organization, the feelings of national inferiority, and so on, completely stunted the potential for development and the normal functioning ofparliamentary life. At the same time, there was no respite from the diplomatic games of the Balkan states, which, following the division of Macedonia, had aspirations to change the borders in their favor. As a result of the activities carried out by the Internal Macedonian Revolutionary Organization (autonomous), which, aided by Bulgaria, infiltrated armed groups into Macedonia, as well as the retaliation carried out by the Serbian gendarmerie, military and paramilitary formations, the Macedonian people were subjected to awful terrors. In the paltry parliamentary life that existed in Macedonia, the pro-regime Serbian parties dominated, as a result of which the Macedonians were in no position to fulfill their political, national and social needs.